1996
DOI: 10.1097/00007890-199609150-00019
|View full text |Cite
|
Sign up to set email alerts
|

Primary Nonfunction of Islet Grafts in Autoimmune Diabetic Nonobese Diabetic Mice Is Prevented by Treatment With Interleukin-4 and Interleukin-101

Abstract: In isologous islet transplantation in spontaneously diabetic nonobese (NOD) mice, destruction of the islet graft is caused by recurrence of T helper (Th)1-driven insulitis[fnc,1. We established a model of transplantation in which female NOD recipients were rendered diabetic by a single injection of cyclophosphamide (250 mg/kg). Under these conditions, 500 freshly isolated islets from young NOD mice transplanted under the kidney capsule did not lead to normoglycemia within 3 day after transplantation, but under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 33 publications
1
31
0
2
Order By: Relevance
“…Transgenic IL-4 NOD mice were protected from insulitis and diabetes, a significantly higher ratio of mitogen-induced IFN-g/IL-4 was found in diabetic NOD mice but not in age-matched non-diabetic NOD mice and treatment of isologous islet transplants with the Type 2 T helper cell-associated cytokines IL-4 and IL-10 in spontaneously diabetic nonobese recipients restored immediate function of the grafts [16,22,23]. Induction of functional tolerance to islet antigens is indicated by the failure of diabetogenic spleen cells to induce diabetes in transgenic NOD-IL-4 recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transgenic IL-4 NOD mice were protected from insulitis and diabetes, a significantly higher ratio of mitogen-induced IFN-g/IL-4 was found in diabetic NOD mice but not in age-matched non-diabetic NOD mice and treatment of isologous islet transplants with the Type 2 T helper cell-associated cytokines IL-4 and IL-10 in spontaneously diabetic nonobese recipients restored immediate function of the grafts [16,22,23]. Induction of functional tolerance to islet antigens is indicated by the failure of diabetogenic spleen cells to induce diabetes in transgenic NOD-IL-4 recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemistry studies showed that IL-10/Fc treatment promoted expression of IL-4 and IL-10, type 2 T helper cytokines, by isletinfiltrating leucocytes [25]. Primary non-function of islet grafts is prevented by treating the recipients with a combination of IL-4 and IL-10, via downregulation of type 1 T helper cytokines [22].…”
Section: Discussionmentioning
confidence: 99%
“…The low frequency of islet grafting is dependent on poor islet recovery from donors [4] and early islet loss during the first hours after grafting [5,6], termed primary graft nonfunction. Islet transplantation exposes cells to a variety of stressful stimuli, notably proinflammatory cytokines that encourage beta cell death and lead to early graft failure [7][8][9]. The reduction in islet mass immediately after transplantation implicates beta cell death by apoptosis and the prerecruitment of intracellular death-signalling pathways [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the islet isolation procedure itself destroys cellular and noncellular components of the pancreas that probably play a role in supporting islet survival (10,12). Further islet transplantation exposes cells to a variety of stressful stimuli, notably proinflammatory cytokines that encourage ␤-cell death and lead to early graft failure (13)(14)(15). Regardless of the molecular mechanisms involved, a reduction in islet ␤-cell mass after transplantation implicates islet ␤-cell death by apoptosis and the prerecruitment of intracellular deathsignaling pathways (16,17).…”
mentioning
confidence: 99%